Perception of Farmers and other Stakeholders about Merits and Demerits of Contract Farming - Biswas, Arnab; Singh, Baldeo; Singh , Premlata (Indian Journal of Extension Education, 2014)
The study was conducted on potato contract farming under Pepsi Co. in Burdwan district of West Bengal. Two villages  were selected randomly from Memari I block of Burdwan district. Twenty five contract farmers were selected randomly  from each of the two villages. Another 20 major stakeholders which included 10 Pepsi Co. staffs and 10 development  officers were selected randomly for the study. A majority of the respondents in the study perceived that the contract  farming provided assured price to the farmers. The extension specialists of the company provided reliable technical  guidance to the farmers. Except seed, the firm did not help the farmer to get other inputs for potato cultivation but it helped  the farmers to get institutional credit easily. Contract farming removes the role of middleman from the markets. The  contracting company introduces various new technologies for the farmers which make the farmers more skilled and  technologically sound in potato cultivation.
Keywords: Contract farming; perception; stakeholders